2023
DOI: 10.1002/ente.202201099
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solar‐Photo(Electro)catalysis of Microwave‐Hydrothermal Synthesized BiVO4, ms‐BiVO4/Reduced Graphene Oxide/Ag3PO4 Nanohybrid: Crystalline Phase‐Dependent Interfacial Charge Carrier Dynamics

Abstract: Bismuth vanadate with reduced graphene oxide (BiVO4/RGO) is prepared via ultrafast, energy‐efficient microwave‐assisted hydrothermal technique. Subsequently, Ag3PO4 nanoparticles are decorated on BiVO4/RGO by impregnated solution process. Photoelectrochemical (PEC) performance is carried out using as‐synthesized ternary heterostructure ms‐BiVO4/RGO/Ag3PO4 nanohybrid photoanode film and Pt‐wire as cathode in 0.5 m Na2SO4 electrolyte solution under AM 1.5 G (100 mW cm−2) irradiation. An enhanced photocurrent den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 79 publications
0
25
0
Order By: Relevance
“…Subsequently, the velocity of the dipoles in the precursor mixture was also increased as they tried to align with the oscillating electromagnetic field provided by the reactor system. 54 Thus, adequate thermal energy was created that facilitated the creation of “hot spots” that favoured burst nucleation as in the case of La Mer crystallization. 50 Accordingly, the electromagnetic radiation, directly interacts with the reactants, thereby creating an energetic coupling at the molecular level, thus further enhancing the growth of the APbI 3 metal halide perovskite powders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the velocity of the dipoles in the precursor mixture was also increased as they tried to align with the oscillating electromagnetic field provided by the reactor system. 54 Thus, adequate thermal energy was created that facilitated the creation of “hot spots” that favoured burst nucleation as in the case of La Mer crystallization. 50 Accordingly, the electromagnetic radiation, directly interacts with the reactants, thereby creating an energetic coupling at the molecular level, thus further enhancing the growth of the APbI 3 metal halide perovskite powders.…”
Section: Resultsmentioning
confidence: 99%
“…50 Accordingly, the electromagnetic radiation, directly interacts with the reactants, thereby creating an energetic coupling at the molecular level, thus further enhancing the growth of the APbI 3 metal halide perovskite powders. 53,54 For a typical APbI 3 metal halide perovskite synthesis, the conversion of reactants into their final products occurs as shown in eqn (1.7).Pb(Ac) 2 + 3HI + CH 3 NH 2 /A(Ac) 2 → APbI 3 + CH 3 COOH…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Recently, we have successfully demonstrated that the hybrid heterostructure of ms-BiVO 4 /RGO/Ag 3 PO 4 showed significant PEC performance by way of an enhanced photocurrent density of 3.6 mA cm −2 with a retention of 24 h, which is 2.3-folds greater than that of pristine ms-BiVO 4 , owing to the enhanced hole diffusion length and minority carrier lifetime. 20 Upon heteroatom doping in the BiVO 4 , leading to effective tuning of valence band (VB) and conduction band (CB) positions of the BiVO 4 photoelectrodes, since the band edge positions substantially determine the redox competence of the photogenerated charge carriers, it directly affects the efficiency of the PEC performance. 19 Moreover, multiple-ion doping into either the A-site or B-site or both sites in the ABO 4 scheelite structure of BiVO 4 has been explored for the superior tunability of the VB and CB electronic structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our recent study, we established the impact of reduced graphene oxide (RGO) as an excellent electron-shuttling mediator with a large specific surface area on ms-BiVO 4 /RGO/Ag 3 PO 4 hybrid photoanode for enhanced PEC activity in freshwater. 20 Indeed, it is expected that the hybrid photoanode surface enhances the electron transfer kinetics at their interface due to the delocalized electrons from the conjugated sp 2 -bonded carbon with a 2-D electronically conductive pathway and the presence of active electrochemical sites, which may benefit direct seawater electrolysis. 36 However, fundamental knowledge on the electronic structure, site-selective doping, oxygen vacancies (OV), and space-charge layer width that could be of benefit to obtain substantially proficient BiVO 4 photoelectrodes remains unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%